2020
DOI: 10.1038/s41529-020-00131-8
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic feasibility of the four-stage chloride-induced depassivation mechanism of iron

Abstract: The atomistic mechanism of chloride-induced depassivation of iron is still debated. A recent study suggests a four-stage depassivation mechanism, in general agreement with the point defect model. The proposed four-stage mechanism is based on reactive force field molecular dynamics simulations and is rather complex but here we use density functional theory to confirm the thermodynamic feasibility of the proposed mechanism. We find that the four surface species, formed in the four stages, have decreasing surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…13 On the other hand, DFT calculations have made some progress towards clarifying the atomic process involved in the oxide breakdown caused by Cl − . [14][15][16][17][18] However, how the oxide film thickness and alloy doping affect the Cl − ingress into Al oxide is still missing in theoretical simulations.…”
mentioning
confidence: 99%
“…13 On the other hand, DFT calculations have made some progress towards clarifying the atomic process involved in the oxide breakdown caused by Cl − . [14][15][16][17][18] However, how the oxide film thickness and alloy doping affect the Cl − ingress into Al oxide is still missing in theoretical simulations.…”
mentioning
confidence: 99%
“…We consider the fully Cl-adsorbed surface, i.e., eight Cl on the surface. Note that unlike Cl adsorption on the oxide surface such as Fe 2 O 3 , ,, where Fe can coordinate with more than one Cl, we found that Mn is energetically unfavorable to coordinate with more than one Cl on the MnS slab (see Figure S7 in the Supporting Information for details). It is shown that Cl interacts vigorously with the surface, especially on the top layer, showing that significant thermodynamic instability is induced.…”
Section: Resultsmentioning
confidence: 82%
“…In recent years, atomistic/molecular modeling techniques have been used to study passivity and chloride-induced depassivation of iron in alkaline electrolytes to develop a fundamental understanding of how chlorides interact with passive films at the molecular level in idealized systems. [109][110][111][112][113][114] Although these techniques have the potential to help future development of new corrosion inhibitors and corrosionresistant steels, they are not very useful or practical in improving forecasts of safety and sustainability of reinforced concrete structures experiencing corrosion. Machine learning is a field that has received increased attention from researchers studying steel corrosion in concrete and has been shown to be a promising approach for predicting damage in reinforced concrete structures experiencing corrosion.…”
Section: Improved Approaches To Forecasting Corrosion Of Steel In Con...mentioning
confidence: 99%